HYPERMASCULINITY IN THE CROODS FILM: A DESCRIPTIVE STUDY - Budianto, Lestari; Amaliyah, Salwa; Sugiarti, Dwi Wahyu (Universitas Islam Sumatera Utara (UISU), 2022)
In the world of literary research, a film is a very interesting object of research. A film is a literary work that can provide a lot of values to human life. This study aims to explore the hypermasculinity that exists in the 3D animated film entitled The Croods. The film was released in 2013 and tells the story of a family led by a man named Grug. This study uses a descriptive qualitative method and the data from this research are formed from two types of data, namely the main data and supporting data. The main data of this study was obtained from the film